Contingency Management Programs in Corrections: Another Panacea? - Gendreau, Paul (Journal of contemporary criminal justice, 2018)
The mantra of best practices in corrections, while well intended, may lead to iatrogenic consequences. Community corrections and prisons are under increasing pressures to manage their caseloads; moreover, the current accountability and get-tough agenda in corrections demands offenders take on more responsibility for their behaviors. As a consequence, we predict more episodes of “panaceaphilia” or quick fix solutions because corrections jurisdictions in the United States are under tremendous pressure to handle their populations at this point in time. In this article, we focus on contingency management programs as the potential next panacea, not because they do not have a proven track record of success, but because they require highly skilled staff and make great demands upon correctional agencies’ decision-making practices. To help counteract panaceaphilia from happening with contingency management, we describe the theory and practice of contingency management, the demands they place on programmers, the type of research needed to evaluate their effectiveness, and how to prevent these programs from turning into punitive punishment regimes.